1993
DOI: 10.1103/physrevb.47.13782
|View full text |Cite
|
Sign up to set email alerts
|

Growth model for metal films on oxide surfaces: Cu on ZnO(0001)-O

Abstract: The structural and electronic properties of Cu films vapor deposited on the oxygen terminated ZnO(OOOl)-0 surface at 130 K have been characterized using x-ray photoemission spectroscopy (XPS), He+ -ion-scattering spectroscopy, low-energy electron diffraction work-function and band-bending measurements, angular-resolved XPS, and CO and H 2 0 chemisorption. These results show that Cu is cationic at tiny coverages, but becomes nearly neutral at coverages beyond a few percent. The Cu clusters into two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
151
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(163 citation statements)
references
References 45 publications
12
151
0
Order By: Relevance
“…This is likely when the metal− reactant bond energy exceeds the difference in energy between the metal−metal and metal−support bonds. 48,49 Since a fact of this could be used to regenerate or redisperse the low surface area catalysts, the formation of the metal−reactant complexes should be maximized. A rigorous thermodynamic study on this topic is described here.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely when the metal− reactant bond energy exceeds the difference in energy between the metal−metal and metal−support bonds. 48,49 Since a fact of this could be used to regenerate or redisperse the low surface area catalysts, the formation of the metal−reactant complexes should be maximized. A rigorous thermodynamic study on this topic is described here.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…It has also been suggested that reactants could change the wetting behavior of metal particles, causing them to spread out on supports when the adsorbate−metal bond energy exceeds the difference in energy between the metal−metal and metal−support bonding. 48,49 Moreover, the strong interaction between adsorbate and metal particle could weaken the metal−metal bond, 50 which would facilitate the detachment of the metal adatoms from small particles, and eventually promote sintering and disintegration.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most detailed atomistic * kostas.sarakinos@liu.se description of far-from-equilibrium 3D island formation is based on homoepitaxial systems in which 3D islands (mounds) form by deposition onto existing small islands, followed by atomic-step descent limited by the Ehlrich-Schwöbel barrier [15][16][17][18][19]. However, for weakly interacting film/substrate systems-including Ag/SiO 2 [20][21][22][23][24], Pd/TiO 2 [25], Cu/ZnO [26,27], and Dy/graphene [4,28]-3D islands develop before the initially formed one-atom-high islands are large enough to efficiently capture vapor-phase deposition flux. Moreover, 3D island formation is also known to occur in the absence of deposition flux due to surface restructuring via dewetting [29].…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism that can explain continued growth, beyond the second atomic layer, of 3D islands on weakly interacting substrates is assisted up-stepping [26,27,35], which assumes a reduction in the step ascent barrier, when adjacent layers are separated horizontally by only one atom, due to an attractive force from the upper step edge (see, for example, position x c in Fig. 1(b), for which the ascent barrier E * 1→2 is smaller than the corresponding value E 1→2 at position x b , but larger than E s→1 at x a ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that metals on semiconductors and oxides usually show 3D growth modes [39] instead of atomically smooth (2D) films. However, this problem can be overcome by use of deposition at low temperatures [40,41] or surfactant-mediated growth [42,43], as it modifies the film kinetics.…”
Section: Introductionmentioning
confidence: 99%